2014
DOI: 10.1016/j.mcn.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A novel protective role for the innate immunity Toll-Like Receptor 3 (TLR3) in the retina via Stat3

Abstract: The innate immune system and inflammatory pathways play key roles in numerous diseases of the central nervous system (CNS). Recent evidence indicates that innate immunity induces both pathogenesis and protection during neuronal injury. To test the possibility that the conflicting roles of innate immunity in the CNS depends on the cellular environment in which innate immunity is stimulated, we analyzed the effect of toll-like receptor 3 (TLR3) activation on neuronal survival in the presence and absence of oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 53 publications
3
41
0
Order By: Relevance
“…The mice were first anesthetized by intraperitoneal injection of a xylazine-ketamine mixture and the eyes were locally anesthetized with eye drops containing 0.5% proparacaine hydrochloride (Akorn, Lake Forest, IL). Mice were then subretinally injected with either 2 μl of paraquat (PQ, 1mM) or saline control, as described [13]. Briefly, an incision was made in the conjunctiva and the sclera and injections were performed using a 1.5 cm 33-gauge Hamilton needle (Hamilton Company, Reno, NV) between the RPE and neural retina.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mice were first anesthetized by intraperitoneal injection of a xylazine-ketamine mixture and the eyes were locally anesthetized with eye drops containing 0.5% proparacaine hydrochloride (Akorn, Lake Forest, IL). Mice were then subretinally injected with either 2 μl of paraquat (PQ, 1mM) or saline control, as described [13]. Briefly, an incision was made in the conjunctiva and the sclera and injections were performed using a 1.5 cm 33-gauge Hamilton needle (Hamilton Company, Reno, NV) between the RPE and neural retina.…”
Section: Methodsmentioning
confidence: 99%
“…Retinal function was analyzed two weeks after paraquat injury using electroretinography (ERG), as described [13]. The mice were dark adapted and then anesthetized with a ketamine/xylazine cocktail and the pupils were dilated with topical 10% phenylepherine hydrochloride.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that STAT3 28,29 and c-Jun N-terminal kinases (JNK3) 30 are key factors in TLR3 activation in retinal cells. We found significant activation of JAK-STAT signaling pathway, but not upregulation of JNK3 in poly I:C-treated retina and 661W cells.…”
Section: Discussionmentioning
confidence: 99%
“…29,44,45 Photoreceptor cell death has been observed in a poly I:C-injected mouse model; however, whether photoreceptor cells respond to dsRNA directly or are affected by RPE dysfunction remains unexplained. Here we have shown that poly I:C treatment induced photoreceptor cell apoptosis, although the underlying mechanisms have not been fully elucidated (Fig.…”
Section: Discussionmentioning
confidence: 99%